Influence of high altitude on C-reactive protein levels in adults with abdominal visceral adiposity - Arteaga-Temoche, Luis (2018)
Objective: To evaluate the influence of high altitude on C-reactive protein (CRP) levels in adults with abdominal visceral adiposity. Materials and methods: A quantitative study with quasi-experimental design, which included twenty-four (24) male medical students from the National University of Trujillo, selected by non-probability convenience sampling and study subject, evaluated at 0 and 4,386 m.a.s.l., and classified according to their degree of abdominal visceral adiposity: normal (G1) and high (G2). Results: The CRP level of G1 in relation to G2 showed no significant difference. Regarding CRP levels, Wilcoxon rank-sum (non-parametric) test was used for G2 and Student´s t-test was used for G1, with significance being shown in both cases. Conclusions: Variations on CRP levels in high altitude compared to sea level in both groups were significant.